1985
DOI: 10.1080/01457638508939636
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Forced-Convective Heat Transfer with Varying Properties in the Entrance Region of Flat Rectangular Ducts

Abstract: Numerical results f or air undergoing laminar forced-convective heat transf er in the entrance region of a fl at rectangular duct with uniform wall temperature are obtained fo r uniform inlet velocity and temperature profiles . The coupled governing partial differential equations are solved in discretized form with proper ty variations being updated through physical property relations . This enables the physical property and thermofluid solutions to converge simultaneously, resulting in a realistic solution to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Numerous studies 20‐28 have been carried out taking into account the effect of temperature‐dependent viscosity for a variety of problems. Akagi and Yoshitani 20 showed that the thermal diffusivity remains almost constant with the change of temperature whereas the viscosity of a high viscous fluid depends on the temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies 20‐28 have been carried out taking into account the effect of temperature‐dependent viscosity for a variety of problems. Akagi and Yoshitani 20 showed that the thermal diffusivity remains almost constant with the change of temperature whereas the viscosity of a high viscous fluid depends on the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of viscous heating and viscosity variations with temperature have been examined in terms of the flow and temperature distribution in a circular pipe 24 . However Maxwell and Ghajar 25 have considered variable fluid properties for the laminar forced convection flow at the entrance of flat rectangular ducts. Herwig et al 26 studied the influence of temperature‐dependent viscosity variations on the momentum and heat transfer in a pipe or channel.…”
Section: Introductionmentioning
confidence: 99%